2012
DOI: 10.1186/1471-2180-12-149
|View full text |Cite
|
Sign up to set email alerts
|

Indication for Co-evolution of Lactobacillus johnsonii with its hosts

Abstract: BackgroundThe intestinal microbiota, composed of complex bacterial populations, is host-specific and affected by environmental factors as well as host genetics. One important bacterial group is the lactic acid bacteria (LAB), which include many health-promoting strains. Here, we studied the genetic variation within a potentially probiotic LAB species, Lactobacillus johnsonii, isolated from various hosts.ResultsA wide survey of 104 fecal samples was carried out for the isolation of L. johnsonii. As part of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 52 publications
2
20
1
2
Order By: Relevance
“…Close similarity could be found between strains from different epidemiological resources, and even within the same host species, such as the tree shrews in this study, and characteristics of high genetic diversity in the isolates were also identified. This unexpected result contradicted previous studies, and several studies have indicated that microorganism specificity to their hosts supports the co-evolution of the host and its microbes [51][52]. However, comparative genomics of the Proteus spp.…”
Section: Discussioncontrasting
confidence: 65%
“…Close similarity could be found between strains from different epidemiological resources, and even within the same host species, such as the tree shrews in this study, and characteristics of high genetic diversity in the isolates were also identified. This unexpected result contradicted previous studies, and several studies have indicated that microorganism specificity to their hosts supports the co-evolution of the host and its microbes [51][52]. However, comparative genomics of the Proteus spp.…”
Section: Discussioncontrasting
confidence: 65%
“…For identification of the species within the L. johnsonii cluster, whole-genome sequencing was performed for 31 isolates (16 from Scotland and 15 from France). Sequences of selected housekeeping genes were used to compare isolates with publicly available sequences of L. johnsonii, L. gasseri, and L. taiwanensis using a Multi-locus Sequence Typing (MLST) approach developed for L. johnsonii [21]. As expected, these three species formed distinct phylogenetic clusters (Fig.…”
Section: Composition Of the Lactobacillus Population In The Gut Of Wimentioning
confidence: 65%
“…The two taxa that consistently dominate Lactobacillus population in the murine gut in both molecular and culture-based studies are L. reuteri and closely related species of the L. johnsonii cluster (e.g., L. johnsonii and L. taiwanensis) [16][17][18][19][20]. Both L. reuteri and L. johnsonii have been shown to be composed of host-specific subpopulations [10,21] and partition resources during gut colonization [22]. These findings suggest a long-term tripartite evolutionary relationship between these two lineages and their rodent host.…”
Section: Introductionmentioning
confidence: 99%
“…En forma similar, Larsson et al (2014) presentan otras propiedades bactericidas y antiinflamatorias (Arokiyaraj et al, 2014). Así como efectos positivos sobre el alimento para cerdas al final de la gestación y durante la lactancia (Buhnik-Rosenblau et al, 2012) y muchas bacterias nativas del BAL es considerada potencialmente probiótica y de gran interés para la industria alimentaria y farmacéutica (Pridmore et al, 2004).…”
Section: Resultados Y Discusiónunclassified